Society-Oriented Social Responsibility Compass to Sustainable Growth of Small and Medium Enterprises in Developing Countries (Global Journal of Management and Business Research, 2020)
Although Society-oriented Social Responsibility has customarily been linked with large companies Small and Medium Enterprises businesses proved to be a considerable sector in developing countries economy Globally Small and Medium Enterprises constitute as productive drivers of inclusive economic growth and development of many countries In South Africa Small and Medium Enterprises make up 91 percent of formalised businesses providing employment to about 60 percent of the labour force and accounts for total economic output of roughly 34 percent Gross Domestic Product GDP of the country Given the critical socioeconomic role played by Small and Medium Enterprises it is vital that they grow and succeed While a number of studies have acknowledged access to finance as a key success factor
Keywords: society-oriented social responsibility; small and medium enterprises; and sustainable growth